2016
DOI: 10.18632/oncotarget.12152
|View full text |Cite
|
Sign up to set email alerts
|

Metavir and FIB-4 scores are associated with patient prognosis after curative hepatectomy in hepatitis B virus-related hepatocellular carcinoma: a retrospective cohort study at two centers in China

Abstract: Although Metavir and Fibrosis-4 (FIB-4) scores are typically used to assess the severity of liver fibrosis, the relationship between these scores and patient outcome in hepatocellular carcinoma (HCC) is unclear. The aim of this study was to evaluate the prognostic value of the severity of hepatic fibrosis in HBV-related HCC patients after curative resection. We examined the prognostic roles of the Metavir and preoperative FIB-4 scores in 432 HBV-HCC patients who underwent curative resection at two different me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…[ 3 ] Several studies have shown the prognostic significance of FIB-4 index, PLR, and NLR score in postsurgery patients with HCC. [ 10 , 13 , 14 ] In this study, a novel index, defined as INS, based on systemic inflammatory response and nutritional status, was developed. The prognostic value of the INS in patients with HCC who underwent surgery was evaluated in 2 independent cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 ] Several studies have shown the prognostic significance of FIB-4 index, PLR, and NLR score in postsurgery patients with HCC. [ 10 , 13 , 14 ] In this study, a novel index, defined as INS, based on systemic inflammatory response and nutritional status, was developed. The prognostic value of the INS in patients with HCC who underwent surgery was evaluated in 2 independent cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 , 6 ] Moreover, there is a wealth of evidence to suggest that systemic inflammation can predict the outcome of survival and recurrence after surgical resection in HCC. [ 7 ] Interestingly, several studies have previously shown that some serum parameters such as markers of systemic inflammation, including platelet count (PLT), hemoglobin, fibrosis index based on the 4 factors (FIB-4) index, neutrophil–lymphocyte ratio (NLR), and platelet–lymphocyte ratio (PLR), have been developed to predict survival of a variety of human cancers, [ 8 13 ] including HCC. [ 14 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…Disease progression was described in terms of METAVIR score, a liver biopsy staging system that assesses the severity of liver fibrosis. 40 METAVIR scores assess the degree of scarring or fibrosis of the liver, ranging from F0 (no fibrosis) to F4 (cirrhosis). Health states were categorized in 2 main phases of disease progression: fibrosis progression stages F0 to F4, and nonfibrosis progression after stage F4.…”
Section: Methodsmentioning
confidence: 99%
“…Health states included healthy (no HCV), no fibrosis (F0), portal fibrosis with no septa (F1), portal fibrosis with few septa (F2), numerous septa without cirrhosis (F3), compensated cirrhosis (F4), decompensated cirrhosis, hepatocellular carcinoma, post–hepatocellular carcinoma, liver transplantation, and post–liver transplantation. 40 , 41 , 42 Without treatment, patients in the F0 state might experience spontaneous clearance of the HCV and return to a no HCV state in state F0. Otherwise, patients may progress to the next severity state of the disease ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 512 consecutive HCC patients undergoing curative resection were selected for retrospective analysis. Of these selected, 46 patients were excluded, according to the inclusion and exclusion criteria described previously [ 8 ]. Briefly, (1) all patients tested HBV surface antigen (HBsAg) and HBV-DNA loads; (2) reliable laboratory test data including liver function; (3) the absence of preoperative extrahepatic metastases confirmed by computed tomography (CT) and/or magnetic resonance imaging (MRI) scanning; (4) no preoperative anticancer therapies; (5) complete resection of all tumor nodules; (6) complete patient records and follow-up data; (7) survival for more than 30 days after surgery.…”
Section: Methodsmentioning
confidence: 99%